2022
DOI: 10.1111/pala.12593
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny and evolution of the elasmosaurid neck highlight greater diversity of Antarctic plesiosaurians

Abstract: The Antarctic plesiosaurian record is critical for understanding the evolution of elasmosaurids in the southern hemisphere. Elasmosaurids exhibit some of the most remarkable modifications of the vertebrate axial skeleton given their extreme elongation of the cervical region. Despite a considerable amount of information available on vertebral counts within Plesiosauria throughout the decades, we have a considerably more limited understanding of the diversity of cervical vertebral shapes in elasmosaurids and how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
(128 reference statements)
0
7
0
Order By: Relevance
“…O’Keefe and Hiller [203] discovered complex ontogenetic allometry in elasmosaurids. Brum et al [204] enhanced this conclusion by revealing a morphological shift in cervicals from disc-like to can-shaped in all elasmosaur groups. For polycotylids, O’Keefe et al [205] and Byrd [206] reported allometric growth in propodials and girdle elements respectively.…”
Section: Preliminaries To Plesiosaur Reconstructionmentioning
confidence: 97%
See 1 more Smart Citation
“…O’Keefe and Hiller [203] discovered complex ontogenetic allometry in elasmosaurids. Brum et al [204] enhanced this conclusion by revealing a morphological shift in cervicals from disc-like to can-shaped in all elasmosaur groups. For polycotylids, O’Keefe et al [205] and Byrd [206] reported allometric growth in propodials and girdle elements respectively.…”
Section: Preliminaries To Plesiosaur Reconstructionmentioning
confidence: 97%
“…In cervical width-BSL regression, three out of eight samples included in the dataset are juveniles. The growth pattern of pliosaur vertebrae has not been studied, but it is possible that cervical ratios of juveniles are different from those of adults, as in elasmosaurids [203, 204]. In cervical width-BSL regression, the juveniles gather at lower ends of the axes due to their small sizes, and this may lead to biased estimates.…”
Section: Reconstructing Missing Puzzles In Plesiosaur Fossilsmentioning
confidence: 99%
“…Representatives of the family Polycotylidae Williston, 1908 in general had short, stout necks and an elongated rostrum (Druckenmiller & Russell, 2008; Frey et al, 2017; Fischer et al, 2018). Similar to polycotylids, elasmosaurids possessed numerous pointy teeth, but had extremely long necks and a short rostrum (Everhart, 2006; Kubo et al, 2012; Brum et al, 2022). Both groups had four morphologically similar flippers that enabled them to move efficiently through the water using all limbs simultaneously, a way of propulsion also used by marine turtles and penguins often referred to as subaqueous flight or ‘flying under water’ (Robinson, 1975; Massare, 1994; Caldwell, 1997; Carpenter & Sanders, 2010; Muscutt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite such limitations, several vertebrate remains have been discovered in Antarctica over the past few decades. These discoveries include plesiosaurs (e.g., O'Gorman et al 2019; Brum et al 2022), pterosaurs (Kellner et al 2019), and dinosaurs (Lamanna et al 2019); for an updated survey of fossil vertebrates in the Upper Cretaceous of Antarctica, see Reguero et al (2022). Importantly, this includes one ankylosaurian species, Antarctopelta oliveroi Salgado and Gasparini, 2006— although there is some dispute on the validity of this taxon (Arbour and Currie 2016; Rozadilla et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2007, the project PALEOANTAR (organized by the Museu Nacional/Universidade Federal do Rio de Janeiro, Brazil) has been working in the Antarctic Peninsula to shed light on the diversification and evolutionary history of Antarctic ecosystems in the deep past (Lima et al 2021; Kellner 2022; Santos et al 2022), including studies on Mesozoic vertebrates (e.g., Kellner et al 2011, 2019; Brum et al 2022) and invertebrates (e.g., Pinheiro et al 2020; Videira-Santos 2020; Piovesan et al 2021). Here, we report on new ankylosaurian materials recovered from Antarctica during the PALEOANTAR expedition in 2015.…”
Section: Introductionmentioning
confidence: 99%